Implementing general environmental duties: Regulators' perceptions of complementary toolkits. (20th September 2021) - Edwards, Joel; Windholz, Eric; Faulkner, Nicholas; Werbeloff, Lara
Abstract: Statutory general duties prioritise the prevention of harm, placing the onus for compliance on individuals and businesses alike to take steps to manage risks posed by their activities. In the case of general environmental duties specifically, they mandate that all parts of the community minimise the risk of environmental harm from their activities. However, encouraging compliant behaviour across such a diverse cohort is a significant challenge. To assist in meeting this challenge, general duties are supported by a variety of complementary regulatory tools. However, little is known about which complementary tools are used by regulators to support general environmental duties, and which factors may influence their application. This article addresses this knowledge gap, with a focus on Anglosphere countries where the use of statutory general duties is becoming increasingly popular. Through semi‐structured interviews with staff from environmental and occupational health and safety regulators, we demonstrate that the existence of a complementary tool does not necessarily mean it will be selected, and that staff responsible for the implementation of general duties are influenced by seven factors. These factors impact not only the selection of complementary tools, but when and how they are applied. The article concludes by discussing implications for practise and future research.